Depression but not non-persistence to antidiabetic drugs is associated with mortality in type 2 diabetes: A nested case-control study. (January 2021) - Lunghi, Carlotta; Zongo, Arsène; Tardif, Isabelle; Demers, Éric; Diendéré, Joël Désiré Relwende; Guénette, Line
Abstract: Aims: To measure the effect of depression on mortality of individuals newly treated with antidiabetic drugs, accounting for non-persistence to treatment. Methods: We conducted a nested case-control study within a cohort of newly treated individuals with diabetes. Using Quebec administrative data, we identified all-cause, diabetes-related, cardiovascular-related and major cardiovascular event deaths during a maximum follow-up of eight years. Each case was matched with up to 10 controls by age, sex, follow-up, and comorbidity index. We used conditional logistic regressions to estimate the effect of depression on mortality, adjusting for non-persistence to antidiabetic drug treatment, and other variables. Results: We retrieved 13, 558 deaths, of which 3, 652 were related to cardiovascular diseases, 2, 112 to major cardiovascular events, and 311 to diabetes. Depression was associated with an increased risk of all-cause and cardiovascular-related deaths, with adjusted odds ratios (ORs) ranging from 1.32 (95% CI: 1.21–1.45) to 1.72 (95% CI: 1.57–1.88) depending on the model, but not with diabetes-related mortality. Conclusion: Depression is independently associated with all-cause and cardiovascular-related mortality in individuals with type 2 diabetes, even when adjusting for non-persistence to antidiabetic drug treatment. Identifying risk factors for depression and implementing a screening and proper treatment for depression may help reducing mortality.